2020
DOI: 10.1123/jcsp.2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

Me, Myself, and My Thoughts: The Influence of Brooding and Reflective Rumination on Depressive Symptoms in Athletes in the United Kingdom

Abstract: Individual differences in vulnerability to depression are still underexplored in athletes. We tested the influence of different brooding and reflective rumination profiles (i.e., repetitive thought processes in response to low/depressed mood) on the odds of experiencing clinically relevant depressive symptoms in competitive athletes (N = 286). The Patient Health Questionnaire–9 and the Ruminative Responses Scale–short form were utilized to measure depression and rumination, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…While both reflective and brooding rumination were correlated with depressive symptoms at T1, only brooding predicted depressive symptoms across the study period. This finding supports initial findings reported by Tahtinen et al (2020), who showed that brooding rumination was more strongly linked to concurrent depressive symptoms than reflective rumination. The findings from the current study also echo results reported among non-athletes, underlining that although both types of rumination correlate with concurrent depression, only brooding predicts depressive symptoms over time (Treynor et al, 2003).…”
Section: Brooding Reflection and Depressive Symptomssupporting
confidence: 92%
See 1 more Smart Citation
“…While both reflective and brooding rumination were correlated with depressive symptoms at T1, only brooding predicted depressive symptoms across the study period. This finding supports initial findings reported by Tahtinen et al (2020), who showed that brooding rumination was more strongly linked to concurrent depressive symptoms than reflective rumination. The findings from the current study also echo results reported among non-athletes, underlining that although both types of rumination correlate with concurrent depression, only brooding predicts depressive symptoms over time (Treynor et al, 2003).…”
Section: Brooding Reflection and Depressive Symptomssupporting
confidence: 92%
“…To-date only one study has explicitly tested depressive rumination in relation to depressive symptoms in athletes. In a study by Tahtinen et al (2020), findings suggested that athletes with high levels of brooding rumination were significantly more likely to exhibit clinically significant depressive symptoms than athletes with low levels of brooding. Reflective rumination, however, increased the likelihood of experiencing clinically significant depressive symptoms only in athletes with high, but not low, levels of brooding.…”
Section: Relevance Of Depressive Rumination In Elite Athletesmentioning
confidence: 99%
“…One of the aims of this study was, therefore, to explore sum scores from the perspective of DSM criteria. Several studies in athletes have utilized PHQ-9 scores ≥10 as a cutoff for identifying clinically relevant cases and reporting prevalence rates (Bell et al, 2016;Du Preez et al, 2017;McGuire, Ingram, Sachs, & Tierney, 2017;Silva-Rocha, de Sousa, & Osório, 2019;Tahtinen et al, 2020;Tahtinen & Kristjansdottir, 2019). We, however, speculated that when applying this cutoff, athletes could attain clinically significant scores without exhibiting the core symptoms of depression (i.e., lack of interest and depressed mood).…”
Section: Prevalence Of Specific Symptomologymentioning
confidence: 99%
“…However, as discussed by several authors (e.g. Nixdorf et al, 2013;Tahtinen et al, 2020;Wolanin et al, 2016), samples have often consisted of a relatively small number of athletes across different sports, and therefore, comparisons have tended to focus on differences between broader sport categories, such as team and individual sports (e.g., Beable et al, 2017;Nixdorf et al, 2013). Consequently, to better understand potential sport-specific differences, scholars have underlined that future studies should aim to include larger samples across specific sports (Golding et al, 2020;Junge & Feddermann-Demont, 2016;Junge & Prinz, 2019;Nixdorf et al, 2013;Wolanin et al, 2016).…”
mentioning
confidence: 99%
“…Among these are: reducing anxiety (but this mode of thinking does nothing but maintain anxiety); resolving situations (in reality it is not so because the person remains firm and rigid, does not elaborate concrete and effective alternatives); "emotional shield, " that is, the person thinks that the brooding keeps him in a state of alarm and therefore keeps him ready to face the feared situation; ascopic brooding, the subjects are not able to explain the reasons why they brood, so the brooding seems to have no precise purpose and for this reason it is seen as something uncontrollable from which it is difficult to escape. Brooding is a construct of rumination and it can be associated to anxiety, depressive symptoms and psychological distress (Michael et al, 2007;Egan et al, 2013;Tahtinen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%